PENGARUH LOCUS OF CONTROL, NEED FOR ACHIEVEMENT, DAN PROACTIVE PERSONALITY TERHADAP INTENSI BERWIRAUSAHA SISWA SMA DI KABUPATEN GRESIK - Wardana, Dewita Windiartya; Ghofur, Muhammad Abdul (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The role of personality attributes in entrepreneurial intentions is still a hot topic of debate among researchers. This research aims to investigate the influence of locus of control, need for achievement, and proactive personality on the entrepreneurial intentions of high school students in Gresik Regency. A total of 341 high school students in Gresik Regency participated in this research. Research data was collected using three instruments, namely locus of control, need for achievement, and proactive personality, which were then analyzed using a quantitative approach, namely the multiple linear regression model. The results of the research showed that students' intentions to start their own business were significantly positively influenced by locus of control, need for achievement, and proactive personality, both partially and simultaneously. The R-square result is 0.763, which means the contribution of the independent variable to the dependent variable is 76.3%, and the remaining 23.7% is determined by other factors outside the model. This supports recent findings that state that personality attributes have a significant contribution in shaping a person's entrepreneurial intentions. It is recommended that educational institutions or schools be able to provide an entrepreneurship curriculum that facilitates students' personal characteristics, especially locus of control, need for achievement, and proactive personality. develop students' intentions for building a business.